Exploring the washback effects of a high-stakes English test on the teaching of English in Spanish upper secondary schools - Amengual Pizarro, Marian (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2010)
In the past decades, there has been a growing interest in the effects of language tests, especially high-stakes tests, on teaching and learning referred to as ‘washback'. In fact, high-stakes tests have started to be exploited to reform instruction and achieve beneficial washback. This paper focuses on the washback effects of a high-stakes English Test (ET) on the teaching of English. The main goal of this study is to examine the washback effects of the ET on the following aspects of teaching: curriculum, materials, teaching methods, and teaching feelings and attitudes. The study also attempts to discover teachers' perceptions towards the introduction of a speaking and a listening component in the design of the new ET due to be implemented in 2012. The overall findings, collected from a questionnaire carried out among 51 secondary teachers, indicate that the ET is clearly affecting curriculum and materials. Results also reveal that the ET appears to influence teachers' methodology. Furthermore, most of the teachers believe that the introduction of a speaking and a listening component in the new ET design will help solve the mismatch between the communicative approach they seem to value and the skills so far evaluated in the ET.